1980
DOI: 10.1152/ajpheart.1980.239.2.h206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tyrosine infusion in normotensive and hypertensive rats

Abstract: To clarify further the action of acute administration of L-tyrosine in lowering blood pressure, L-tyrosine ethylester was infused intravenously into awake [deoxycorticosterone acetate (DOCA)-salt] hypertensive rats, two-kidney Goldblatt hypertensive rats, and normotensive rats. The effects of tyrosine were measured on arterial pressure, heart rate, plasma catecholamine levels, and plasma renin activity. Blood pressure and heart rate were lowered in all groups despite significant elevation of plasma dopamine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

1983
1983
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…We believe that the hypotensive properties of APM in SHR are due to its metabolite TYR, an amino acid previously shown to decrease BP in SHR (Sved et aL, 1979), and DOCA-salt treated rats (Bresnahan et al, 1980). Other investigators have found that APM administration can indeed enhance brain norepinephrine synthesis and release in rats (Yokogoshi et aL, 1984) and mice (Coulombe and Sharma, 1985).…”
Section: Discussionmentioning
confidence: 82%
“…We believe that the hypotensive properties of APM in SHR are due to its metabolite TYR, an amino acid previously shown to decrease BP in SHR (Sved et aL, 1979), and DOCA-salt treated rats (Bresnahan et al, 1980). Other investigators have found that APM administration can indeed enhance brain norepinephrine synthesis and release in rats (Yokogoshi et aL, 1984) and mice (Coulombe and Sharma, 1985).…”
Section: Discussionmentioning
confidence: 82%
“…The study by Bresnahan et al [6] is poten tially the most informative with regard to attenuation of blood pressure in the DOCAsalt-treated, hypertensive rat. These investi gators were unable to demonstrate a hypoten sive influence of Tyr when 3.0 mg of Tyr ethyl ester/min/kg of body weight was in fused intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly ele vated brainstem Tyr content in Tyr-treated rats provides proof that supplementation of Purina laboratory chow with Tyr can in crease brain levels of this amino acid. While the influence of chronic treatment with Tyr on blood pressure seems tenuous, there is abundant and consistent information that acute administration of Tyr can reduce blood pressure [6,10,35], including an acute hypo tension in the SHR [29,35] and the DOCAsalt-treated rat [6]. The factors accounting for the differences between acute and chronic treatments with Tyr on blood pressure are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation might involve a prolonged activation of catecholaminereleasing neurons in brain-stem vasopressor areas, resulting from the hypertension. Such activation is seen in DOCA-salt-treated and genetically hypertensive rats (Chalmers, 1975;Sved el aL, 1979) and in that species tyrosine decreases BP while increasing CNS norepinephrine release (Sved et aL, 1979;Bresnahan et aL, 1980;Osumi et aL, 1974). If this explanation is accurate it seems remarkable that, in our previously hypertensive dogs the vasodepressor mechanisms predominated, even in the face of profound hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamines are synthesized from the amino acid tyrosine, and tyrosine administration has been shown to accelerate their production when those neurons happen to be physiologically active and firing frequently Carlsson and Lindqvist, 1978). Tyrosine thus can affect sympathetic outflow, acting peripherally to increase BP in rats made hypotensive by hemorrhage (Conlay et al, 1981); and centrally to decrease BP in genetically hypertensive or DOCA-salt-treated rats (Sved et aL, 1979;Bresnahan et aL, 1980;Osumi et al, 1974). The present experiments examine the effect of tyrosine on BP in another animal model, the hypotensive dog.…”
Section: Introductionmentioning
confidence: 99%